Transcriptome and 2-DE proteome analyses reveal defense-associated development in the leaf galls induced by psyllids on Machilus japonica var. kusanoi - Tin-Han Shih; Jian-Liang Chen; Meng-Yuan Huang (Botanical Studies)
Abstract Background Galls are abnormal plant tissues that result from the interaction between the defense responses of plants and the activities of galling herbivores. During infection, secondary metabolites are synthesized to mitigate the oxidative stress whereas growth and cellular processes in infected tissues are reprogrammed. Although the regulatory networks of growth-related phytohormones are recognized as the main component in gall formation, other factors like oxidative stress might also being critical in gall development. In this study, we focused on the spherical psyllid galls found in the leaves of Machilus japonica var. kusanoi to analyze the differences in transcript, protein content, and several metabolites between galls and leaves. Results Early gall tissues were enriched in cell cycle regulation and organization genes, suggesting processes, such as mitosis, meiosis, and microtubule-based movement. Proteins such as CAM7, LSH6, and eIF2β, associated with seed development, were highly expressed in early gall tissues. We demonstrated a significant role for ROS-related stress responses in early gall development. Higher amount of polyphenols, which are well-known antioxidants, was found in gall tissue as well. Conclusions This study provides valuable insights into the mechanisms underlying gall development and enhances our understanding of this complex process. Future research should explore the impact of ROS modulation on gall tissue development and assess phytohormone content at various psyllid larval and gall stages to elucidate the regulatory network involved in gall morphogenesis.